Gambaran Pengetahuan Orang Tua Tentang Edukasi Seks pada Remaja di Desa Kauditan Tahun 2023 - Desiska Pricilia Tumatar; Atik Sunarmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Introduction: Adolescence is a vulnerable period regarding information about sex. Teenagers need people around them, especially parents, to guide them in providing sex education. Therefore, parents must have the knowledge and insight to help teenagers understand sex as early as possible. Objective: to find out the description of parents' knowledge about sex education for teenagers. Method: This research uses a descriptive method with a cross sectional approach. The total sample was 30 respondents. Results: of the 30 respondents, 11 respondents had a good level of knowledge, while there were 10 respondents in the sufficient category and 9 respondents in the poor category. Conclusion: 4 respondents graduated from junior high school, 18 respondents graduated from high school and 8 respondents graduated from bachelor's degrees. Of the respondents who were junior high school graduates, 1 respondent had sufficient knowledge and 2 respondents had insufficient knowledge. There were 5 respondents who graduated from high school who had good knowledge, 6 respondents who had sufficient knowledge and 7 respondents who had poor knowledge. Of the 8 respondents who graduated from bachelor's degrees, 5 respondents had good knowledge, 2 had sufficient knowledge and 1 respondent had poor knowledge.